Laser Spot Melting on Ti-6Al-4V Substrates: A Study on Thermal History and Keyhole Porosity. (September 2022) - Haddad, Marwan; Nixon, Karlie; Sellers, Ronald; Anez Lijeron, Guillermo; Wang, Hui; Gould, Benjamin; Wolff, Sarah J.
Abstract: In situ monitoring techniques have been applied to laser spot welding experiments to study specific phenomena that also occur in metal additive manufacturing processes. Without the interference of powder particles and their interaction with the laser beam, melt pool signatures and pore evaluation can be monitored, which can help in understanding their effect on the end results in laser spot welding and in metal additive manufacturing. One in situ monitoring technique is thermography which uses infrared cameras to acquire surface temperatures in real time. However, one of the main challenges for infrared cameras is finding the unknown emissivity value of printed parts. Another challenge is that thermography cannot monitor the dynamics under the surface of the substrate. A new method was proposed by combining X-ray imaging and infrared imaging to estimate the emissivity and monitor subsurface phenomena. The method consisted of measuring the melt pool size in X-ray images and comparing it to infrared images. The proposed method was tested by analyzing X-ray and infrared images from laser spot melting experiments on Ti-6Al-4V substrates. Ti-6Al-4V is widely used in metal additive manufacturing processes because of its attractive mechanical properties consequently estimating its emissivity is important. The laser power and laser dwell time were varied for each experiment, and the process was observed in real-time using X-ray and infrared images. The objective was to achieve a confidence interval of the emissivity value for Ti-6Al-4V. In addition, an emissivity value was selected from the obtained confidence interval, which enabled the analysis of the thermal history of the surface of the substrate. Furthermore, the resulting emissivity was used to correct the reading of the temperatures and to estimate the melt pool size in the infrared images. The selected emissivity value of 0.5 from the confidence interval gave an accurate estimation of the melt pool size with an overall average error percentile with the melt pool size measured with the X-ray images of approximately 6.5%. After the temperature correction, solidification time, solidification rates and cooling rates were also calculated from the infrared images using the thermal history. Lastly, it has been observed that the size of the pore generated by the keyhole could affect the surface dynamic of the substrates, concluding that defects under the surface might be detected using thermal images from infrared cameras.